Cobalt-molybdenum-based heterostructure composite material loaded on nitrogen-doped porous carbon as well as preparation method and application of cobalt-molybdenum-based heterostructure composite material

By supporting cobalt-molybdenum-based heterostructure composite materials on nitrogen-doped porous carbon, the problems of easy accumulation of a single transition metal compound during the catalysis process, insufficient active sites and poor conductivity are solved, and efficient and stable hydrogen evolution reaction performance is achieved.

CN119530870AActive Publication Date: 2025-02-28JIANGXI NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411807882.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the prior art, a single transition metal compound has problems such as easy accumulation, insufficient exposure of active sites and poor conductivity during the catalysis process, which limits its efficiency and stability in electrocatalytic hydrogen evolution reaction.

Method used

By loading the cobalt-molybdenum-based heterostructure composite on nitrogen-doped porous carbon, the material's ability to dissociate water molecules and adsorb/desorb hydrogen species using the heterostructure of a variety of transition metals (Co, Mo) and their compounds is enhanced.

Benefits of technology

The hydrogen evolution reaction (HER) performance is significantly improved, the overpotential is reduced, the catalytic efficiency is improved, and the stability is maintained during long-term continuous catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530870A_ABST
    Figure CN119530870A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalytic hydrogen evolution, and particularly relates to a cobalt-molybdenum-based heterostructure composite material loaded on nitrogen-doped porous carbon and a preparation method and application of the cobalt-molybdenum-based heterostructure composite material. The cobalt-molybdenum-based heterostructure composite material comprises nitrogen-doped porous carbon, Co crystals, Mo2C crystals and Co3Mo3N crystals, wherein the Co crystals, the Mo2C crystals and the Co3Mo3N crystals are loaded on the nitrogen-doped porous carbon; the content of Co in the cobalt-molybdenum-based heterostructure composite material is 2wt%-8wt%; and the content of Mo in the cobalt-molybdenum-based heterostructure composite material is 10 wt%-30 wt%. The nitrogen-doped porous carbon structure is adopted as a carrier to provide enhanced attachment sites for mass transfer of an electrolyte and a product, and meanwhile, a large number of active sites can be remarkably exposed in a water electrolysis hydrogen evolution reaction by combining a cobalt-molybdenum-based heterostructure loaded on the nitrogen-doped porous carbon structure; the composite material shows efficient activity, and can still keep stable activity and structure after continuous catalytic hydrogen production for 20 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrocatalytic hydrogen evolution, and specifically relates to a cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon, and a preparation method and application thereof. Background Art

[0002] The emergence of severe challenges such as global warming and fossil fuel depletion is mainly due to the widespread use of non-renewable energy. Hydrogen (H2), due to its ultra-high energy density, is considered to be the most promising clean energy carrier in the future. However, although precious metal-based catalysts (such as Pt / C) have ideal performance, their high cost limits their feasibility in large-scale practical applications. Therefore, there is an urgent need to develop efficient, stable and low-cost electrocatalytic hydrogen evolution catalysts to promote the widespread application of hydrogen energy. Summary of the invention

[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon and a preparation method and application thereof, specifically adopting the following technical solutions: In the first aspect, the present invention provides a cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon, the cobalt-molybdenum-based heterostructure composite material comprising nitrogen-doped porous carbon and Co crystals, Mo2C crystals, and Co3Mo3N crystals supported on the nitrogen-doped porous carbon, the content of Co in the cobalt-molybdenum-based heterostructure composite material is 2 wt%-8 wt%; the content of Mo in the cobalt-molybdenum-based heterostructure composite material is 10 wt%-30wt%.

[0004] The present invention constructs a heterogeneous structure of multiple transition metals (Co, Mo) and their compounds on porous carbon, and utilizes the synergistic effect generated by the interaction between heterogeneous components to enhance the material's ability to dissociate water molecules and absorb / desorb hydrogen species, and effectively improve its hydrogen evolution reaction (HER) performance. This solves the problems of easy accumulation, insufficient exposure of active sites, and poor conductivity of single transition metal compounds in the catalytic process in the prior art.

[0005] The present invention constructs a heterostructure of multiple transition metals (Co, Mo) and their compounds loaded on porous carbon, wherein the interface of the crystalline phase with ternary hydrogen evolution activity is combined to form a nanoparticle heterojunction, which can more efficiently promote charge transfer, thereby enhancing the dissociation effect of the metal site on water molecules and the ability to adsorb / desorb hydrogen species; and the nitrogen-doped porous carbon provides a good and stable conductive support for the dispersed ternary heterojunction, and is also conducive to the exposure of more active sites. Therefore, the composite material can effectively improve its hydrogen evolution reaction (HER) performance.

[0006] As a further preferred embodiment, in the cobalt-molybdenum-based heterostructure composite material, heterostructure nanoparticles are formed by Co crystals, Mo2C crystals and Co3Mo3N crystals, and the particle size of the heterostructure nanoparticles is 5 nm to 20 nm.

[0007] As a further preferred embodiment, the lattice distance in the cobalt-molybdenum-based heterostructure composite material corresponds to Co (111), Mo2C (101) and Co3Mo3N (331). In the present invention, the three crystal phase crystal planes of Co (111), Mo2C (101) and Co3Mo3N (331) are all active crystal planes of hydrogen evolution reaction. Combining them on nano-scale particles can significantly enhance charge transfer, reduce the overpotential of hydrogen evolution reaction, and thus improve catalytic efficiency.

[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon, comprising the following steps: The mixed solution of urea and anhydrous citric acid is dripped into the ethanol solution containing cobalt salt and molybdenum salt, and stirred to form a uniform sol; then the sol is heated and stirred to form a gel, and dried to obtain a composite material precursor powder; The composite material precursor powder is placed in a tube furnace, maintained in a flowing hydrogen / argon mixed atmosphere, and subjected to high-temperature annealing treatment to obtain the cobalt-molybdenum-based heterogeneous structure composite material supported on nitrogen-doped porous carbon.

[0009] The present invention adopts a liquid phase method to prepare a uniform Co and Mo complex sol as a precursor, then heats and stirs the Co and Mo complex sol at a constant temperature to evaporate the sol to form a Co and Mo compound gel, which is then dried as a composite material precursor, and finally a cobalt-molybdenum-based heterogeneous structure composite material supported on nitrogen-doped porous carbon is obtained through a high-temperature annealing reaction.

[0010] As a further preferred embodiment, the volume ratio of the mixed solution of urea and anhydrous citric acid to the ethanol solution containing cobalt salt and molybdenum salt is 2:15. In the present invention, if the ratio is too high, the metal content of the cobalt-molybdenum-based heterostructure in the composite material will be reduced; if the ratio is too low, the cobalt-molybdenum-based heterostructure nanoparticles in the composite material will be aggregated, which will lead to a decrease in the catalytic activity of hydrogen evolution.

[0011] As a further preferred embodiment, the urea mass concentration is 350 mg·mL -1 ~ 400 mg mL -1 The mass concentration of anhydrous citric acid is 40 mg·mL -1 ~ 50 mg mL -1In the preparation process of the present invention, the concentration of urea and anhydrous citric acid is the key to forming nitrogen-doped porous carbon in the composite material; if the concentration is too low, it cannot provide conductive support for the composition of cobalt-molybdenum-based heterostructure nanoparticles; if the concentration is too high, too much nitrogen-doped porous carbon is formed, which will cause a decrease in the proportion of cobalt-molybdenum-based heterostructure nanoparticles and reduce the active sites of the hydrogen evolution reaction.

[0012] As a further preferred embodiment, the cobalt salt is CoCl2·6H2O solution; the molybdenum salt is MoCl5; the mass concentration of the CoCl2·6H2O solution is 0.90 mg·mL -1 ~ 1.00 mg mL -1 The mass concentration of MoCl5 is 4.00 mg·mL -1 ~ 5.00 mg mL -1 In the preparation process of the present invention, the concentration of the metal salt within the above range is conducive to the controllable formation of a ternary metal crystalline phase nanoparticle heterojunction inside the composite material.

[0013] As a further preferred embodiment, the heating and stirring temperature is 65°C to 85°C, and the heating and stirring time is 1 h to 3 h; the drying temperature is 90°C to 120°C, and is maintained for 8 h to 12 h. In the preparation process of the present invention, heating for too long and at too high a temperature will cause the structure of the composite material precursor to be destroyed, and it will be difficult to form a cobalt-molybdenum-based heterostructure composite material on nitrogen-doped porous carbon later; and heating and stirring for too short a time and at too low a temperature will excessively prolong the formation time of the precursor.

[0014] As a further preferred embodiment, the specific parameters of the high temperature annealing treatment are as follows: At 5 ℃·min -1 The heating rate was increased from room temperature to 400 °C, then maintained for 1 h to 3 h, and then increased at 5 °C min -1 The heating rate was increased to 900 ℃~1100 ℃, then maintained for 1 h~3 h, and finally cooled naturally to room temperature.

[0015] In a third aspect, the present invention provides the use of the above-mentioned cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon as an electrocatalyst in the electrolysis of water and hydrogen evolution reaction.

[0016] The beneficial effects of the present invention are: (1) The present invention uses nitrogen-doped porous carbon structure as a carrier to provide enhanced attachment sites for mass transfer of electrolyte and product. At the same time, the cobalt-molybdenum-based heterostructure loaded on the nitrogen-doped porous carbon structure can significantly expose a large number of active sites in the hydrogen evolution reaction of water electrolysis. This composite material shows high activity, especially in generating 10 mA cm-2 At current density, only a very low overpotential (83 mV) and a very small Tafel slope (56.5 mV dec -1 ). In addition, the composite material can still maintain stable activity and structure after continuous catalytic hydrogen production for 20 hours.

[0017] (2) The preparation method provided by the present invention is simple and highly reproducible, and the raw materials used are cheap and easily available. In addition, the cobalt-molybdenum heterostructure hydrogen evolution electrocatalytic composite material obtained by this method exhibits good electrical conductivity because the active material is loaded on nitrogen-doped porous carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 Shown is the XRD pattern of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon.

[0020] Figure 2 Shown is the EDX-Mapping image of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon.

[0021] Figure 3 Shown is the SEM image of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon.

[0022] Figure 4 Shown is the TEM image of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon.

[0023] Figure 5 Shown are the linear voltammetric sweep polarization curves of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon as an electrocatalyst in 1 M KOH.

[0024] Figure 6 Shown is the Tafel slope curve of the cobalt-molybdenum-based heterostructure composite supported on nitrogen-doped porous carbon as an electrocatalyst.

[0025] Figure 7 The cobalt-molybdenum-based heterostructure composite supported on nitrogen-doped porous carbon was used as an electrocatalyst at a constant 10 mA·cm –2 Chronopotentiometry curves of the test at the current density for 20 h.

[0026] Figure 8Shown is the SEM image of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon as an electrocatalyst after undergoing a 20 h chronopotentiostatic stability test. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The crystal structure of the product prepared by the present invention is determined by an X-ray diffractometer (XRD), the morphology of the material is determined by a scanning electron microscope (SEM) and a transmission electron microscope (TEM), the elemental composition is determined by energy dispersive X-ray spectrometer imaging (EDX-mapping), and the catalytic activity of hydrogen evolution by electrolysis of water is measured on a Shanghai Chenhua electrochemical workstation.

[0029] Example 1 A method for preparing a cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon, which specifically comprises the following steps: (1) Prepare 10 mL of deionized water solution containing 3.8 g of urea and 0.4572 g of anhydrous citric acid, add it to 75 mL of ethanol solution containing 0.328 g of CoCl2·6H2O and 0.071 g of MoCl5 mixed metal salt, and stir for 10 min to form a uniform sol; then place the sol in a heat-collecting magnetic stirrer and continue stirring, and evaporate it at 75 °C for 1.5 h to form a gel; place the gel in an oven at 100 °C and dry it for 10 h to form a composite material precursor; (2) Weigh 1.5 g of the composite material precursor and place it in the center of a tube furnace. Maintain a flowing hydrogen / argon mixed atmosphere and set the temperature program for high temperature annealing. The high temperature annealing program is: 5 °C min -1 The heating rate was increased from room temperature to 400 °C, then maintained for 2 h, and then increased at 5 °C min -1 The heating rate was increased from 400 ℃ to 1000 ℃, then maintained for 2 h, and finally cooled naturally to obtain a cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon.

[0030] The cobalt-molybdenum-based heterostructure composite material loaded on nitrogen-doped porous carbon prepared above was characterized and tested for performance (XRD, EDX-mapping, SEM, TEM). The specific results are as follows Figure 1-Figure 4 As shown: Depend on Figure 1X-ray powder diffraction (XRD) analysis revealed that the obtained cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon contained Co, Mo2C, and Co3Mo3N crystals; energy dispersive X-ray spectrometer imaging (EDX-mapping, see Figure 2 ) analysis proved that the elements Co, Mo, N and C were uniformly distributed in the composite material, among which Co and Mo elements were aggregated in the form of particles; scanning electron microscope photos (see Figure 3 ) shows that the composite material is assembled from a large number of crystalline particles and a nitrogen-doped porous carbon substrate, and its surface is rich in rough structures; transmission electron microscopy photos (see Figure 4 ) showed that a large number of Co / Mo2C / Co3Mo3N crystalline particles were loaded on nitrogen-doped porous carbon to form a heterogeneous composite material.

[0031] From the above, it can be seen that the present invention constructs a heterostructure of multiple transition metals (Co, Mo) and their compounds on porous carbon, wherein the crystalline phase interface of the ternary hydrogen evolution activity is combined to form a nanoparticle heterojunction, which can more efficiently promote charge transfer, thereby enhancing the dissociation effect of the metal site on water molecules and the ability to adsorb / desorb hydrogen species; and the nitrogen-doped porous carbon provides a good and stable conductive support for the dispersed ternary heterojunction, and is also conducive to the exposure of more active sites. Therefore, the composite material can effectively improve its hydrogen evolution reaction (HER) performance.

[0032] Example 2 The performance test of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon as a catalyst for hydrogen evolution reaction in water electrolysis is as follows: (1) Preparation of electrocatalyst working electrode: 8 mg of cobalt-molybdenum-based heterostructure composite material powder loaded on nitrogen-doped porous carbon was mixed with 2 mg of Super P and 17 μL of 10 wt% PTFE solution. A small amount of ethanol was added and ground continuously for 30 min to form a uniform catalyst film. The catalyst film was evenly pasted on the nickel foam surface with a pasting area of ​​3 cm −2 , vacuum dried at 60 °C for 12 h, applied a pressure of 7 MPa using a tablet press for 3 min, and cut the catalyst to a paste area of ​​0.5 cm −2 Nickel foam was used as the working electrode.

[0033] (2) Electrochemical performance study: The electrochemical properties of the prepared samples were tested on a CHI 760E electrochemical workstation (Chenhua Instruments, Shanghai, China). A conventional three-electrode system was used, i.e., a graphite electrode as the counter electrode, a saturated calomel electrode (SCE) as the reference electrode, and a catalyst-modified nickel foam as the working electrode. -1 KOH aqueous solution was used as the supporting electrolyte. Unless otherwise specified, all potentials in the test were converted to reversible hydrogen electrode potentials according to the Nernst equation ( E RHE ). Overpotential η It can be further obtained by the following formula: η = -E RHE .

[0034] The above test results are as follows Figure 5-Figure 8 As shown: Figure 5 The cobalt-molybdenum-based heterostructure composite supported on nitrogen-doped porous carbon was used as an electrocatalyst at 1 mol·L -1 Linear voltammetric scanning polarization curve in KOH. The figure shows that the composite material has good electrocatalytic activity. The starting potential of the electrocatalytic water decomposition hydrogen evolution reaction (defined as the current density of 1 mA·cm -2 The overpotential of 10 mA·cm -2 The baseline current density (equivalent to that produced by a 12.3% efficient solar water splitting device) requires only 83 mV overpotential.

[0035] Figure 6 The Tafel slope curve of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon as an electrocatalyst. The figure shows that the composite material has a low Tafel slope (only 56.5 mV·dec -1 ), indicating that with the increase of overpotential, the rate of hydrogen evolution reaction will accelerate sharply.

[0036] Figure 7 Cobalt-Molybdenum-based heterostructure composites supported on nitrogen-doped porous carbon as electrocatalysts at 10 mA cm -2 Chronopotentiometry curves under constant current density. -2 ) During the 20-hour continuous test, only an overpotential of no more than 118 mV needs to be applied; Figure 8 The following is a scanning electron microscope image of the composite material after a 20-hour chronopotential stability test as an electrocatalyst, showing that it still maintains a morphology similar to that of the initial state. These reflect that the material has high electrocatalytic activity and structural stability in alkaline electrolytes.

[0037] The embodiments of the present application are described above in conjunction with the accompanying drawings. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the core idea of ​​the present application, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the inspiration of the present application, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present application and the claims, all of which are within the protection of the present application.

Claims

1. A cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon, characterized in that: The cobalt-molybdenum-based heterostructure composite material includes nitrogen-doped porous carbon and Co crystals, Mo2C crystals, and Co3Mo3N crystals loaded on the nitrogen-doped porous carbon. The content of Co in the cobalt-molybdenum-based heterostructure composite material is 2 wt%-8 wt%; the content of Mo in the cobalt-molybdenum-based heterostructure composite material is 10 wt%-30wt%.

2. The cobalt-molybdenum-based heterostructure composite material according to claim 1, characterized in that: In the cobalt-molybdenum-based heterostructure composite material, heterostructure nanoparticles are formed by Co crystals, Mo2C crystals and Co3Mo3N crystals, and the particle size of the heterostructure nanoparticles is 5 nm to 20 nm.

3. The cobalt-molybdenum-based heterostructure composite material according to claim 1, characterized in that: The lattice distances in the cobalt-molybdenum-based heterostructure composite material correspond to Co (111), Mo2C (101) and Co3Mo3N (331).

4. The method for preparing the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon according to any one of claims 1 to 3, characterized in that: The following steps are involved: The mixed solution of urea and anhydrous citric acid is dripped into the ethanol solution containing cobalt salt and molybdenum salt, and stirred to form a uniform sol; then the sol is heated and stirred to form a gel, and dried to obtain a composite material precursor powder; The composite material precursor powder is placed in a tube furnace, maintained in a flowing hydrogen / argon mixed atmosphere, and subjected to high-temperature annealing treatment to obtain the cobalt-molybdenum-based heterogeneous structure composite material supported on nitrogen-doped porous carbon.

5. The preparation method according to claim 4, characterized in that: The volume ratio of the mixed solution of urea and anhydrous citric acid to the ethanol solution containing cobalt salt and molybdenum salt is 2:

15.

6. The preparation method according to claim 5, characterized in that: The urea mass concentration is 350 mg·mL -1 ~400 mg mL -1 The mass concentration of anhydrous citric acid is 40 mg·mL -1 ~ 50 mg mL -1 .

7. The preparation method according to claim 5, characterized in that: The cobalt salt is CoCl2·6H2O solution; the molybdenum salt is MoCl5; the mass concentration of the CoCl2·6H2O solution is 0.90 mg·mL -1 ~ 1.00 mg mL -1 The mass concentration of MoCl5 is 4.00 mg·mL -1 ~ 5.00 mg mL -1 .

8. The preparation method according to claim 4, wherein the heating and stirring temperature is 65°C to 85°C, and the heating and stirring time is 1 h to 3 h; the drying temperature is 90°C to 120°C, and is maintained for 8 h to 12 h.

9. The preparation method according to claim 4, characterized in that: The specific parameters of the high temperature annealing treatment are as follows: At 5 ℃·min -1 The heating rate was increased from room temperature to 400 °C, then maintained for 1 h to 3 h, and then increased at 5 °C min -1 The heating rate was increased to 900 ℃~1100 ℃, then maintained for 1 h~3 h, and finally cooled naturally to room temperature.

10. An application of the cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon according to any one of claims 1 to 3, characterized in that: The cobalt-molybdenum-based heterostructure composite material supported on nitrogen-doped porous carbon is used as an electrocatalyst for electrolyzing water to generate hydrogen.

Citation Information

Patent Citations

  • Confined-range Co3Mo3N-Co heterostructure composite material as well as preparation method and application thereof

    CN117165995A